Alphaworld: some things keep changing - Porter, Anna (Horwitz Education St. Leonards, N.S.W., 2005)
"Some Things Keep Changing" is a contemplative exploration of the constant flux of life and its impact on personal identity and relationships. Through a series of poignant reflections and anecdotes, the narrative examines how change influences our perceptions, aspirations, and connections with others. It highlights the inevitability of transformation, urging readers to embrace uncertainty and find strength in adaptability. With a focus on growth and resilience, the work encourages a deeper understanding of life's cycles, fostering a sense of hope and acceptance in the face of change.